Efficiently Photocontrollable or Not? Biological Activity of Photoisomerizable Diarylethenes. Issue 44 (3rd July 2018) - Komarov, Igor V.; Afonin, Sergii; Babii, Oleg; Schober, Tim; Ulrich, Anne S.
Abstract: Diarylethene derivatives, the biological activity of which can be reversibly changed by irradiation with light of different wavelengths, have shown promise as scientific tools and as candidates for photocontrollable drugs. However, examples demonstrating efficient photocontrol of their biological activity are still relatively rare. This concept article discusses the possible reasons for this situation and presents a critical analysis of existing data and hypotheses in this field, in order to extract the design principles enabling the construction of efficient photocontrollable diarylethene‐based molecules. Papers addressing biologically relevant interactions between diarylethenes and biomolecules are analyzed; however, in most published cases, the efficiency of photocontrol in living systems remains to be demonstrated. We hope that this article will encourage further discussion of design principles, primarily among pharmacologists, synthetic and medicinal chemists. Abstract : Drugs for photopharmacology : The development of diarylethene‐based biologically active molecules is critically analysed. This concept article suggests design principles that should be accounted for in the construction of efficient photocontrollable molecules containing diarylethene‐based molecular switches.